2022
DOI: 10.1038/s41598-022-24893-0
|View full text |Cite
|
Sign up to set email alerts
|

Perturb and optimize users’ location privacy using geo-indistinguishability and location semantics

Abstract: Location-based services (LBS) are capable of providing location-based information retrieval, traffic navigation, entertainment services, emergency rescues, and several similar services primarily on the premise of the geographic location of users or mobile devices. However, in the process of introducing a new user experience, it is also easy to expose users’ specific location which can result in more private information leakage. Hence, the protection of location privacy remains one of the critical issues of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…The comparative analysis of algorithms involved Geo-I [ 9 ], which utilized Euclidean distance; GG-I [ 10 ], which employed undirected graph distance based on Geo-I; and the work of Yan et al [ 11 ] marked as POLS (location perturbation and optimization algorithm), which integrated Geo-I with location semantics while still relying on Euclidean distance. In contrast, our proposed metric incorporates semantic, temporal, and query information alongside road network direction, aiming for enhanced location distinguishability.…”
Section: Analysis and Experimental Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The comparative analysis of algorithms involved Geo-I [ 9 ], which utilized Euclidean distance; GG-I [ 10 ], which employed undirected graph distance based on Geo-I; and the work of Yan et al [ 11 ] marked as POLS (location perturbation and optimization algorithm), which integrated Geo-I with location semantics while still relying on Euclidean distance. In contrast, our proposed metric incorporates semantic, temporal, and query information alongside road network direction, aiming for enhanced location distinguishability.…”
Section: Analysis and Experimental Resultsmentioning
confidence: 99%
“…Realistically, there are one-way and two-way streets in real life, and the undirected graph still deviates from the metric of the actual road network. According to different application scenarios, Geo-I has been extensively explored, incorporating various aspects such as location semantics [ 11 ], distribution of personnel directions [ 12 ], and personalized user requirements [ 13 , 14 ], but the distinguishability metric remains consistent with Geo-I.…”
Section: Relates Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Xiong et al 21 combined the location obfuscation of geo-indistinguishability with the path optimization of spatial crowd-sourcing to provide strong privacy protection with minimal cost. Yan et al 22 suggested to combine location semantic information with geo-indistinguishability in order to reduce the probability of semantic inference attack and improve the quality of location service.…”
Section: Related Workmentioning
confidence: 99%